PTU-119 Histopathology and Long Term Clinical Prognosis in HCV. does the Biopsy still have anything to Add?. (4th June 2013) - White, M; John, J; Swann, R E; Thomson, E; Mills, P
Abstract : Introduction: Hepatitis C (HCV) was first characterised in 1989 and most UK sufferers are infected in early adulthood. While a cirrhosis rate of 20% over 20 years is often quoted, life-long outcomes and factors predicting these are not fully defined. With increasing availability of noninvasive markers of fibrosis, liver biopsy is now rarely performed at diagnosis. This study aims to explore the value of baseline liver biopsy in determining long-term clinical prognosis. Methods: Patients were identified from a historical HCV study cohort (n = 202) at one centre who had a diagnostic liver biopsy at baseline (between 1984 and 2004) and available follow up data. Clinical and histologic data were recorded. Kaplan-Meier plots of time to cirrhosis and multivariate Cox regression were performed. Results: 146 patients had adequate follow up data. The mean duration of follow up from presumed date of infection was 22 (SD 8.51) years with a mean follow up from biopsy of 10 years (SD 5.3). The majority of patients were male 90 (62%) and had been infected through IV drug use 81 (55%). 58 patients (40%) had Genotype 1 infection. From baseline biopsies, 44 (30%) had moderate and 12 (8%) severe steatosis. 93 (64%) had Ishak fibrosis scores of 0 or 1 at baseline, 34 (23%) 2–3 and 10 (7%) 4–5. 9 patients (6%) had cirrhosis at baseline. A total of 31 (21%) developed clinical cirrhosis during follow up. From these, 11 decompensated and 5 developed hepatocellular carcinoma. Factors associated with shorter time to cirrhosis were later age at diagnosis (HR: 1.08, 95%CI 1.03–1.13) and increasing Ishak fibrosis score (HR: 2.13, 95%CI 1.59–2.85). The 10 year cirrhosis free survival from baseline biopsy was 93% for Ishak fibrosis scores of 0 or 1, compared with 78% and 27% for scores 2&3 and 4&5 respectively (see Fig 1 .). 95 (65%) patients were treated, of whom 64 (67%) achieved a sustained virological response (SVR) with standard treatment. History of alcohol excess, genotype 1 and severe steatosis were significant negative predictors of SVR. Conclusion: The rate of cirrhosis was similar to that expected over a 20 year period. Higher baseline fibrosis scores were associated with earlier development of cirrhosis and steatosis was a negative predictor of SVR. Overall, important prognostic information is available from initial diagnostic biopsies and may be useful in determining timing of treatment. Disclosure of Interest: None Declared